Handbook of the economics of conflict - Dube, Oeindrila; Morelli, Massimo; Ray, Debraj 1957- (North-Holland, an imprint of Elsevier, 2024)
Handbook of the Economics of Conflict highlights new advances in the field, with this new volume presenting interesting chapters written by an international board of authors. Chapters in this release include Conflict Initiation and the Coase Theorem, Misperceptions and the dynamics of conflict, Power Mismatch, Shocks and Conflict, On the Salience of Ethnic Conflict, Polarization and Conflict, Trade Policy in the Shadow of War: A Quantitative Toolkit for Geoeconomics, Conflict in History, Strategic militarization, Propaganda and Conflict, Climate and Conflict, and The Psychology of Conflict.